Relationship between births and deaths during the Covid-19 Pandemic in Brazil (Research, Society and Development, 2022)
The Covid-19 pandemic started in December 2019 in China and in March of the same year in Brazil, impacted the healthcare structure which, due to its expansion in recent decades, was able to absorb a large part of the patients of this new disease. Despite the robustness of the Brazilian Unified Health System, the country was among those that had the most deaths related to the new corona virus and its associated diseases. At the same time, for the second consecutive year there was a lower number of births in the country, anticipating an assessment of expected vegetative growth for approximately ten years. In an article published in the same periodical last year, we explored the panorama of deaths and Intensive Care Units, especially children, in Brazil. We found that we could forcibly have an increase in the number of beds and with the decrease in births in the country, we can stay close to the values ​​recommended by the Pediatrics Societies. Here we aim to maintain the pattern of analysis of the dead and the born, with a focus on those under twenty. The methodology used was a systematic review with exploration of related literature and public databases. The data suggest that Brazil is in a process of vegetative growth. This is due to a reduction in the number of births in the last two years compared to 2019 and a significant increase in deaths directly related to the new Corona virus pandemic. An important fact is that Covid-19 affects children and adolescents and that the decrease in cases is associated with intense vaccination in the country.